Effectiveness of pelvic floor muscle training for treating urinary incontinence in female athletes: A critically appraised topic - Finley, A.; Romesburg, L., Baumann, S. G.; Yannaccone, A.; Crane, P. (International Journal of Athletic Therapy & Training, 2025)
Objective: To investigate the effectiveness of pelvic floor muscle training in treating urinary incontinence in female athletes aged over 13 years.